Effect of Socialization of Government Internal Control System (SPIP) on the understanding and application in Health Polytechnic of Semarang - Soesanto Soesanto; Tri Wiji Lestari; Ardi Soesilo Wibowo (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2014)
Government Internal Control System (SPIP ) is a process that is integrated into the actions and activities carried out continuously by managers and all employees for achieving agency's objectives through good governance, including effective and efficient, the reliability of financial reporting, safeguarding state assets, and obedience against legislation. Managers and employees in the departments and representatives of Health Polytechnic of Semarang need to understand and apply the SPIP in creating good governance. Quantitative research with quasi-experimental methods was used in this study. Sample was 51 managers and employees of the departments and representatives Health Polytechnic of Semarang. All gathered in a room and took a pre-test questionnaire about understanding and applying the elements of socialization SPIP. Socialization of SPIP was then provided. A post-test questionnaire similar to the pre-test with SPIP was taken by the participants in an interval of one month. Data processing was done with the editing, coding, data entry and tabulation of data. Univariate and bivariate analysis as well as Wilcoxon matched pairs test were used to analyze the data. The results showed that understanding of the elements and application of SPIP increased after the socialization. There is a before and after effect of socialization with SPIP application in Health Polytechnic of Semarang. As a suggestion, we need to make the application of SPIP and commitment of managers, employees, and representatives of Health Polytechnic of Semarang in order to create good governance.